Use of Complementary and Alternative Medicine in a Large Sample of Anxiety Patients - Bystritsky, Alexander (2012)
OBJECTIVE: To examine a large sample of patients with anxiety and the association between types of complementary and alternative treatments that were used, demographic variables, diagnostic categories, and treatment outcomes. METHOD: Cross-sectional and longitudinal survey during the Coordinated Anxiety Learning and Management (CALM) study that assessed this intervention against the Usual Care in a sample of patients with anxiety recruited from primary care. Interviewer-administered questionnaires via a centralized telephone survey by blinded assessment raters. The interviews were done at baseline, 6, 12, and 18 months of the study. A total of 1004 adults ages 18–75 who met DSM-IV criteria for Generalized Anxiety Disorder (GAD), Panic Disorder, Social Anxiety Disorder, or Post-Traumatic Stress Disorder. We assessed medication/herbal use, the use of any alternative therapies, and combined Complementary and Alternative Medicine (CAM) use. RESULTS: We found an extensive (43%) use of a variety of CAM treatments that is consistent with previous study results in populations with anxiety. Only a few significant demographic or interventional characteristics of CAM users were found. Users most often had a diagnosis of GAD, were older, more educated, and had two or more chronic medical conditions. CAM users who had a 50% or more drop in anxiety scores over 18 months were less likely to report continued use of alternative therapies. CONCLUSIONS: The study confirms the importance of awareness of CAM use in this population for possible interference with traditional first-line treatments of these disorders, but also for finding the best integrative use for patients who require multiple treatment modalities.